The short‐term dynamics of posttraumatic stress disorder symptoms during the acute posttrauma period. Issue 4 (15th November 2019) - Price, Matthew; Legrand, Alison C.; Brier, Zoe M. F.; Gratton, Jennifer; Skalka, Christian
Abstract: Background: The manner in which posttraumatic stress disorder (PTSD) develops remains largely unknown. PTSD is comprised of 20 symptoms across 4 clusters. These clusters were hypothesized to reflect a failure of recovery model in which intrusive symptoms appear first. Intrusive symptoms led to avoidance of trauma‐related stimuli, which resulted in sustained arousal. The sustained arousal ultimately led to dysphoria. Methods: This hypothesized symptom progression was evaluated during the acute posttrauma period (the first 30 days postevent). Participants ( N = 80) reported their PTSD symptoms for 30 days via mobile devices. Using a short‐term dynamic modeling framework, a temporal and contemporaneous model of PTSD symptoms was obtained. Results: In the temporal network, a fear‐conditioning component was identified that supported the hypothesized set of relations among symptom clusters. The contemporaneous network was classified by two subnetworks. The first corresponded to a fear‐conditioning model that included symptoms of intrusions and avoidance. The second included symptoms of dysphoria and arousal. Conclusions: These findings suggest that, after a trauma, there may be a fear‐conditioning process that involves intrusions, avoidance, and arousal symptoms. Dysphoric symptoms were also present but developed as a partially distinct component.